Association of the chromodomain helicase DNA‐binding protein 4 (CHD4) missense variation p.D140E with cancer: Potential interaction with smoking. Issue 2 (19th November 2014) - Yamada, Miki; Sato, Noriko; Ikeda, Shinobu; Arai, Tomio; Sawabe, Motoji; Mori, Seijiro; Yamada, Yoshiji; Muramatsu, Masaaki; Tanaka, Masashi
<x xml:space="preserve">Abstract</x> Chromodomain helicase DNA‐binding protein 4 (CHD4) plays a pivotal role in chromatin‐remodeling and has been implicated in the development of cancer. The aim of this study is to determine the association of CHD4 gene variants with cancer. Nine missense single nucleotide variations (SNVs) in CHD4 were retrieved from genotyping, by an exome‐chip, 2, 343 consecutive autopsy cases, in which the presence or absence of cancer was pathologically reviewed. The association of CHD4 variants with the presence of cancer and with different types of cancer was determined. Interaction with smoking was also determined. There were 1, 446 patients with cancer and 897 patients without cancer. Of the nine SNVs, eight SNVs were monomorphic, while two nonsynonymous SNVs; rs7479004 (p.D140E) and rs1639122 (p.E139D) were further verified by direct sequencing. The p.D140E was associated with the presence of cancer (adjusted odds ratio [OR], 2.17; 95% confidence interval [CI], 1.37–3.44, P = 0.001), but not p.E139D. The effect size was larger in the smokers (adjusted OR, 4.66; 95% CI, 1.82–11.9; P =0.001), suggesting that there may be a gene environment interaction. For individual cancer types, p.D140E was associated with lung cancer (adjusted OR, 3.99; 95% CI, 2.07–7.67; P < 0.001), malignant lymphoma (adjusted OR, 3.24; 95% CI, 1.43–7.33; P = 0.005), and rectum cancer (adjusted OR, 6.23; 95% CI, 2.31–16.8; P < 0.001). A nonsynonymous SNV of CHD4, p.D140E, confers a risk of cancer and may interact with smoking habit to increase the risk. © 2014 Wiley Periodicals, Inc.